The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6tb00898d
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-stabilized colloidal polyelectrolyte complexes of chitosan/hyaluronan: a tool for the inhibition of HIV-1 infection

Abstract: International audienceZinc(II) stabilized polyelectrolyte nano-complexes (PECs) of chitosan and hyaluronan (HYA) were designed as safe and efficient drug delivery systems. HIV-1 reverse transcriptase inhibitor tenofovir (TF) was quantitatively encapsulated and the particle interface could be functionalized in PBS with targeting proteins such as anti-alpha 4b7 immunoglobulin A. Chitosan-HYA nanoPECs were non-cytotoxic on human peripheral blood mononuclear cells (PBMCs), within the investigated nanoparticle conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The resulting nanocomposite system can target HIV‐enriched human peripheral blood mononuclear cells (PBMCs) with reduced drug toxicity, thereby preventing PBMCs from HIV infection. [ 79 ]…”
Section: Nanomaterials As Carriers Of Approved Antiviral Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting nanocomposite system can target HIV‐enriched human peripheral blood mononuclear cells (PBMCs) with reduced drug toxicity, thereby preventing PBMCs from HIV infection. [ 79 ]…”
Section: Nanomaterials As Carriers Of Approved Antiviral Drugsmentioning
confidence: 99%
“…The resulting nanocomposite system can target HIVenriched human peripheral blood mononuclear cells (PBMCs) with reduced drug toxicity, thereby preventing PBMCs from HIV infection. [79] Inorganic nanomaterials such as mesoporous silica NPs (MSNs) have also been widely used in drug delivery due to their excellent biological safety, high drug loading efficiency, and easy preparation and modification. Amino-functionalized MSNs loaded with drugs of shikimic acid or quercetin can kill pathogenic avian influenza H5N1 virus and showed anti-inflammatory effects additionally.…”
Section: Nanomaterials As Carriers Of Approved Antiviral Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al prepared a polyelectrolyte complex of chitosan with hyaluronan and got the composite stabilized with zinc. The antiviral activity of the developed complex was increased against HIV, which could be attributed to their ability to block the entry point of HIV to the host cell [25] . Li et al prepared an ionic complex of chitosan with sialyloligosaccharides (SOS) and tested against influenza (H1N1) and found that a higher ratio of SOS results in increased adhesion, more cytoprotective and a potential anti-influenza agent [26] .…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…Nevertheless, as it was mentioned above, CH as a native molecule has limited activity as an antimicrobial agent over a wide range of viruses, but substitution at the amino group and hydroxyl group can significantly alter its efficacy against various viral strains [18]. In fact, different CH derivatives have been reported to have potential as anti-HIV agents [19][20][21]. Gao et al have further demonstrated that 3, 6-O-sulfated chitosan was able to inhibit a broad spectrum of HPV pseudoviruses (HPV PV) [22].…”
Section: Introductionmentioning
confidence: 99%